Pengaruh Kegiatan Mewarnai Terhadap Kemampuan Motorik Halus Anak Uisia Dini di TK/PAUD Bersama Simaninggir - Hasibuan, Rahyana; Nasution , Nur Hamida; Daulay, Nur Gabena; Lubis, Lisda Khoiriah; Lubis, Maria (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
This study aims to determine the effect of coloring activities on fine motor skills in early childhood. Fine motor skills involve the coordination of small muscles, especially the hands and fingers, which are essential for children's readiness for later learning. This study used an experimental method, conducted using pre-tests and post-tests. The subjects were 19 children from a kindergarten/early childhood education program (TK/PAUD Bersama) in Simaninggir Village, Sosopan District, Padang Lawas Regency, with fine motor skills as the focus. Data collection techniques used were observation and documentation. The results showed a 20% increase in fine motor skills in the pre-test, with an increase of 80% in the post-test, with children achieving a maximum coloring score of 80. Therefore, coloring activities can be an effective learning strategy to stimulate fine motor development in early childhood education.